2020
DOI: 10.1111/mec.15388
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread selection in shaping the genomic landscape during speciation of Populus

Abstract: Increasing our understanding of how evolutionary processes drive the genomic landscape of variation is fundamental to a better understanding of the genomic consequences of speciation. However, genome‐wide patterns of within‐ and between‐ species variation have not been fully investigated in most forest tree species despite their global ecological and economic importance. Here, we use whole‐genome resequencing data from four Populus species spanning the speciation continuum to reconstruct their demographic hist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 122 publications
0
38
0
Order By: Relevance
“…Although these two species diverged nearly 1 million years ago, reproductive isolations are incomplete between them, possibly because of the large population size and long generation time of Populus species (Wang et al, 2020a, 2020b). This would have resulted in the occurrence of hybrids in the contacting region of the two species in the eastern QTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these two species diverged nearly 1 million years ago, reproductive isolations are incomplete between them, possibly because of the large population size and long generation time of Populus species (Wang et al, 2020a, 2020b). This would have resulted in the occurrence of hybrids in the contacting region of the two species in the eastern QTP.…”
Section: Discussionmentioning
confidence: 99%
“…Both species belong to sect. Populus of the genus Populus L. (Salicaceae), which contains approximately seven species with widespread distribution throughout the Northern Hemisphere (Zhang et al, 2018; Wang et al, 2020a, 2020b). Aspens are commonly recognized as “keystone species” in boreal and temperate forests and usually play a pioneer role following forest disturbance (Edenius et al, 2011; Berrill et al, 2017; Zheng et al, 2017; Fan et al, 2018; Rogers et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive heterogeneity in the extent of admixture across genomes has been reported in multiple studies of closely related species, including trees (Wang et al 2020), insects (Martin et al 2019, Valencia-Motoya et al 2020 and cichlid fish (Gante et al 2016, Svardel et al 2020. Tracts of the southern O. korogwe genome with extensive evidence for hybridization (e.g.…”
Section: Heterogeneity Of Admixture Across the Genomementioning
confidence: 96%
“…Under the process of positive selection, although genetic diversity was reduced, interspecific differentiation increased. Earlier speciation of Populus studies have revealed that apart from background selection, recent positive selection and long-term balancing selection have also been crucial components in shaping patterns of genome-wide variation during the Populus speciation process (Wang et al, 2020). However, since it is difficult to accurately estimate the variation in these highly differentiated regions exhibiting low genetic diversity, more caution is required in interpreting the functional characteristics of the overrepresented genes identified here.…”
mentioning
confidence: 88%